The Pathogenic Role of Long Non-coding RNA H19 in Atherosclerosis via the miR-146a-5p/ANGPTL4 Pathway - Huang, Shi-Feng; Zhao, Guifang; Peng, Xiao-Fei; Ye, Wen-Chu (Frontiers in Cardiovascular Medicine, 2021)
The abnormally expressed long non-coding RNA (lncRNA) H19 has a crucial function in the development and progression of cardiovascular disease; however, its role in atherosclerosis is yet to be known. We aimed to examine the impacts of lncRNA H19 on atherogenesis as well as the involved mechanism. The outcomes from this research illustrated that the expression of lncRNA H19 was elevated in mouse blood and aorta with lipid-loaded macrophages and atherosclerosis. Adeno-associated virus (AAV)-mediated lncRNA H19 overexpression significantly increased the atherosclerotic plaque area in apoE−/− mice supplied with a Western diet. The upregulation of lncRNA H19 decreased the miR-146a-5p expression but increased the levels of ANGPTL4 in mouse blood and aorta and THP-1 cells. Furthermore, lncRNA H19 overexpression promoted lipid accumulation in oxidized low-density lipoprotein (ox-LDL)-induced THP-1 macrophages. However, the knockdown of lncRNA H19 served as a protection against atherosclerosis in apoE−/− mice and lowered the accumulation of lipids in ox-LDL-induced THP-1 macrophages. lncRNA H19 promoted the expression of ANGPTL4 via competitively binding to miR-146a-5p, thus promoting lipid accumulation in atherosclerosis. These findings altogether demonstrated that lncRNA H19 facilitated the accumulation of lipid in macrophages and aggravated the progression of atherosclerosis through the miR-146a-5p/ANGPTL4 pathway. Targeting lncRNA H19 might be an auspicious therapeutic approach for preventing and treating atherosclerotic disease.